2004
DOI: 10.1515/tjj.2004.21.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Forced Convection in Curved Channel with Vortex Structures

Abstract: Theoretical and experimental investigations have been carried out of heat transfer in a curvilinear channel with developed secondary flows. Linear and non-linear effects of vortexes have been studied on heat transfer intensity. Relations in the form of quadratures as well as algebraic equations have been obtained describing these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ligrani and Hedland [7] examined the surface heat transfers and flow structure in a curved channel with laminar, transitional, and turbulent Flows by physical apparatus. Avramenko et al [8] experimentally investigated the laminar forced convection in a curved channel with vortex structures. The investigations found that linear and nonlinear components grew with the Dean number.…”
Section: Introductionmentioning
confidence: 99%
“…Ligrani and Hedland [7] examined the surface heat transfers and flow structure in a curved channel with laminar, transitional, and turbulent Flows by physical apparatus. Avramenko et al [8] experimentally investigated the laminar forced convection in a curved channel with vortex structures. The investigations found that linear and nonlinear components grew with the Dean number.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9], and Yamamoto et al [10], there have not been enough focus on the creation and development of secondary flow curved duct flow (laminar flow, Stokes flow, peristaltic flow, non-isothermal flow, Dean flow). In particular, numerous experimental research on flow investigation in a constant area curved duct have been conducted (Dong and Ebadian [11], Ligrani and Hedland [12], Avramenko et al [13], Biswas et al [14]. Flow on non-aligned straight rotating pipes and curved pipes has been critically examined by Hye and Khan [15,16] as well.…”
Section: Introductionmentioning
confidence: 99%